THE EDUCATION COMMUNICATIVE PARADIGM - Ашиток, Н. І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The intercourse dehumanization is an essential feature that characterizes crisis state of education. Based on intercourse of translator the classic education paradigm exhausted the humanism potential as it interprets educational process as subject – subjective interaction at the last quarter of the 20th century developed countries introduce education paradigm that based on subject intercourse. Its subject –subjective specific represents humanistic tendencies in education in the conditions of informatisation of society and activities computerization.